Work Motivation of Primary Health Workers in China: The Translation of a Measurement Scale and Its Correlation with Turnover Intention - Li H; Yuan B; Yu Y; Li J; Meng Q (Dove Medical Press, 2022)
Huiwen Li,1 Beibei Yuan,2 Yahang Yu,3 Jia Li,4 Qingyue Meng2 1China Population and Development Research Center, Beijing, People's Republic of China; 2China Center for Health Development Studies, Peking University, Beijing, People's Republic of China; 3School of Public Health, Peking University, Beijing, People's Republic of China; 4Department of Health Policy and Management, School of Public Health, Peking University, Beijing, People's Republic of ChinaCorrespondence: Beibei Yuan, China Center for Health Development Studies, Peking University, 38 Xuan Yuan Road, Haidian District, Beijing, 100191, People's Republic of China, Tel +86 01 82805703, Fax +86 01 82805695, Email beibeiyuan@bjmu.edu.cnBackground: High turnover intention, as a manifestation of low work motivation, is a crucial barrier to strengthening primary health systems worldwide, including in China. Targeting those being less motivated will be a realistic choice to retain primary health workers. This study translate, adapt, and validate the Work Motivation Scale for Health Workers (WMSHW) scale to directly measure and rate health workers' motivation composition based on Self-Determination Theory, and assessed how health workers with different levels of motivation being associated with the turnover intention.Methods: The process of translation and cross-cultural adaptation followed the recommendations of international guidelines. Participants include 1341 health workers within 75 primary health institutions from 6 provinces in China. The reliability and validity of the scale was analyzed. Cluster analysis in a person-centered approach and logistic regression analysis was used to understand how different combinations of motivations related to intention to leave.Results: Confirmatory factor analysis indicated that the modified five-factor model had a better fit than the other models in accordance with the original English version. The factor loads were high and ranged from 0.70 to 0.9. Cronbach's alpha coefficients for five dimensions of the Chinese WMSHW ranged from 0.81 to 0.94, indicating the scale's high internal consistency. Four distinct clusters of work motivation were found in this study, representing low motivated, highly controlled, highly autonomous and highly motivated primary health workers. Compared with low motivation group, both controlled and autonomous motivation groups were more likely to have lower turnover intention. The negative relationship between motivation and intention to leave became stronger with the level of motivation increasing: highly controlled cluster (OR: 0.47; 95% CI: 0.35- 0.63), highly autonomous (OR: 0.27; 95% CI: 0.18- 0.41) and highly motivated (OR: 0.20; 95% CI: 0.15- 0.27).Conclusion: The Chinese version of WMSHW showed satisfactory reliability and validity and can be used as an instrument for measuring and rating the work motivation of Chinese health workers. The primary health workers were grouped into four motivation levels based on this scale. Both controlled and autonomous motivation could work in reduce the turnover intention, and the influence of autonomous motivation on retaining was stronger.Keywords: work motivation, health worker, self-determination theory, validation, turnover intention